Газовая чувствительность гексагонального оксида галлия - Алмаев, Дмитрий Александрович (Перспективы развития фундаментальных наук. Т. 1 : сборник научных трудов XX Международной конференции студентов, аспирантов и молодых ученых, 25-28 апреля 2023 г.)
The structural and gas-sensitive properties of ε(κ)-Ga2O3 films obtained by halide vapor phase epitaxy (HVPE) under the exposure to CO, H2 and NH3 were studied. The temperature and concentration dependences of the response and their analysis were presented. A gas sensitivity mechanism was proposed.